Efektivitas Media Pembelajaran Snake And Ladders Terhadap Motivasi Belajar Siswa Kelas VII: Studi Kuasi Eksperimen di SMPIT Al Amri - Al Fikri, Naufal Hilmi; Romiyati; Alfiyanto, Arif Setiawan (Educational Research Center, 2026)
His study aims to examine the effectiveness of using snake and ladders game-based learning media in improving students’ learning motivation at SMPIT Al Amri. The research employed a quantitative approach with a quasi-experimental design. The population consisted of all seventh-grade students of SMPIT Al Amri, totaling 25 students, and the sampling technique used was total sampling. The research instrument was a learning motivation questionnaire based on a five-point Likert scale, which had been tested for validity and reliability. Data analysis was conducted using prerequisite tests, including the Shapiro–Wilk normality test and Levene’s homogeneity test, followed by hypothesis testing using the Independent Samples t-Test with the assistance of SPSS software. The results of the validity test showed that 15 out of 20 questionnaire items were valid, while the reliability test yielded a Cronbach’s Alpha coefficient of 0.797, indicating that the instrument was reliable. The normality test results indicated that the data were normally distributed, and the homogeneity test confirmed that the variances between groups were homogeneous. The hypothesis testing results revealed a significance value of Sig. (2-tailed) = 0.000 (p < 0.05) with a mean differ ence of 21.094, indicating a significant difference in learning motivation between the experimental group and the control group. The findings demonstrate that students who learned using the snake and ladders game-based media had higher learning motivation compared to those who received conventional instruction. Based on these findings, it can be concluded that snake and ladders game-based learning media is effective in enhancing students’ learning motivation, particularly at the junior secondary school level.